Implementasi Teknologi Otomatisasi pada Tahap Pengolahan Kedelai dengan Penerapan Good Manufacturing Practices (GMP) pada Industri Tempe Dusun Sadang Kabupaten Ngawi - Dimas Nur Prakoso; Yuli Prasetyo; Ardila Prihadyatama; Adittio Ramadhan; Narava Kansha Putra Pratama (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community engagement program aims to enhance the productivity and hygiene of household-scale tempe production by automating soybean dehulling and implementing Good Manufacturing Practices (GMP), complemented by strengthened business management. The participatory action approach comprised installation and commissioning of a soybean dehulling machine, GMP implementation sessions with MSME partners, and assistance in obtaining the Business Identification Number (NIB). A pre–post evaluation assessed production capacity (kg/day), cycle time and dehulling yield, GMP compliance, and legal status. The machine was installed and operated stably; dehulling cycle time decreased, dehulling yield was high (≥85%), and daily capacity increased from approximately 30–40 kg/day to 80–100 kg/day. Training produced a hygienic SOP that is followed with routinely completed checklists, alongside indications of reduced product defects. The issuance of the NIB strengthened partners’ readiness to access formal markets and government support. These findings affirm that an integrated techno-managerial intervention effectively improves performance and product quality in Tempe production and is suitable for replication, with emphasis on machine fine-tuning and strict adherence to GMP.